Climate change and occupational health: Are there limits to our ability to adapt? - Marcus Dillender (W.E. Upjohn Institute for Employment Research, 2019)
This study considers the relationship between temperature and occupational health. The results indicate that both high and low temperatures increase injury rates and that high temperatures have more severe adverse effects in warmer climates, which suggests that avoiding the adverse effects of high temperatures may be easier for workers when hot days are rarer. While research on the effect of temperature on mortality finds substantial capacity for adaption with current technology, the results presented here suggest that outdoor workers face challenges in adapting to high temperatures.
Keywords: I1; J2; Q5; 330; adaptation; climate change; labor force participation; occupational health; temperature